2005
DOI: 10.1590/s0102-33062005000200020
|View full text |Cite
|
Sign up to set email alerts
|

Regeneração de espécies nativas lenhosas sob plantio de Eucalyptus em área de Cerrado na Floresta Nacional de Paraopeba, MG, Brasil

Abstract: RESUMO -(Regeneração de espécies nativas lenhosas sob plantio de Eucalyptus em área de Cerrado na Floresta Nacional de Paraopeba, MG, Brasil). A regeneração de sub-bosques em plantios homogêneos tem estreita dependência de florestas vizinhas. Outros fatores exercem influência, como a ecologia da dispersão da espécie, os efeitos de borda e clareiras. Diante disto, procurou-se conhecer a florística e a estrutura da vegetação lenhosa de espécies nativas sob plantio de Eucalyptus em área de Cerrado na Floresta Nac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
2
30

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 11 publications
(5 reference statements)
3
21
2
30
Order By: Relevance
“…Its fruits are small and numerous rosy berries that become jade-green during ripening, with high levels of water and carbohydrates (respectively 76.63 and 13.38%) but low protein content (2.17%) (Maruyama et al, 2007). Neri et al (2005) observed high density of M. albicans occuring in regenerating cerrado areas.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Its fruits are small and numerous rosy berries that become jade-green during ripening, with high levels of water and carbohydrates (respectively 76.63 and 13.38%) but low protein content (2.17%) (Maruyama et al, 2007). Neri et al (2005) observed high density of M. albicans occuring in regenerating cerrado areas.…”
Section: Introductionmentioning
confidence: 68%
“…This vegetation has been greatly reduced by anthropic action, with only several fragments of cerrado remaining in São Paulo state, usually of less than 100 ha each (São Paulo, 1997). Studies have demonstrated that aproximately 50% of cerrado woody species show zoochoric dispersal syndrome (Vieira et al, 2002;Neri et al, 2005). Birds and mammals are believed to be the most important seed dispersers (Howe and Westley, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Já, Tapirira guianensis, Protium spruceanum e Cecropia pachystachya ocorreram, simultaneamente, na baixada e encosta dos braços "A" e "C", bem como Myrsine guianensis ocorreu também, simultaneamente, na baixada e encosta dos braços "B" e "C". Algumas espécies lenhosas que se destacaram em levantamentos fitossociológicos e florísticos realizados em áreas degradadas e/ou perturbadas (ALVARENGA et al, 2006;ARAÚJO et al, 2006;CORRÊA & MÉLO FILHO, 2007;FARIAS et al, 1993;GAVILANES & ANGIERI FILHO, 1991;NAPPO et al, 2004;NERI et al, 2005;PINTO et al, 2005;TABARELLI & MANTOVANI, 1999;VALCARCEL & ALTERIO, 1998;VIEIRA & PESSOA, 2001) De maneira geral, os três braços apresentam composição florística de plantas pioneiras (Tabela 3), o que é comum em ambientes degradados e/ou perturbados (FARIAS et al, 1993;ROY, 1990;TABARELLI & MANTOVANI, 1999).…”
Section: Resultsunclassified
“…Its area of occurrence comprises the states of Minas Gerais, São Paulo, and Mato Grosso do Sul down to Rio Grande do Sul; it is very abundant in the humid regions of montane forests, such as semideciduous forests and pine forests (BRITEZ et al, 1992), and is very common in the Latifoliate Semideciduous Forest of the Paraná River Basin (LORENZI, 2002). Due to its abundant fructification, its fruit is consumed by several bird species and constitutes the favorite food of some Psittacidae such as parrots, in addition to other wild animals (CARVALHO, 2003;NERI et al, 2005). It thrives on well-drained river banks, providing excellent food for fish (MAIXNER;FERREIRA, 1976).…”
Section: Calliandra Brevipes Is a Species That Occurs Mainly From Parmentioning
confidence: 99%